PERENCANAAN KEUANGAN BAGI MASYARAKAT JAMIAH ISLAM SYEIKH DAUD AL-FATHONI (JISDA) THAILAND - Cita Ayni Putri Silalahi; Alistraja D. Sialalahi; Dalmi Iskandar Sultani; Dara Fitrah Dwi; M. Khalid; Abdulrosyid Abdullah (Jurnal Abdimas Bina Bangsa, 2024)
Financial planning is a process of planning expenditure, investment and financing to optimize existing finances. Considering the inportance of personal financial planning in everyday life, the UMN AL Washliyah Community service team provides knowledge about how make financial plans through community service activities. Community service activities were carried out at JISDA Thailand with 40 students as socialization participants. The result of implementing community service, where JISDA Thailand students know and understand what financial planning is how to make good financial planning, the benefits of financial planning and simple bookkeeping. This activity can provide motivation for students to be financially literate in managing their finances. This activity went very well and smoothly.